Public Administration in the Field of Intellectual Property in The USA and The Republic of Uzbekistan - Akhrorkhon A. Nabiraev; Murodiljon O. Orifjonov (Periodica Journal, 2023)
This article provides a comparative analysis of public administration in the field of intellectual property of the United States of America and the Republic of Uzbekistan. For this purpose, first of all, the procedure of public administration on intellectual property in these countries has been disclosed and then a comparative analysis between them was provided
Keywords: Intellectual property; public administration; patent; trademarks